Predicting model for device density of states of Quantum‐Confined SiC nanotube with magnetic dopant - Jafarova, Vusala Nabi; Aliyeva, Mina B; Scurtu, Ionut Cristian (Technium Sustainability, 2024)
Single walled (6,0) gold substituted SiC nanotube systems were studied by first principles modeling. We observed the electronic structures of SiC nanomaterials are significantly modified by the introduction of gold, and SiC:Au nanotube exhibits magnetic response. While the configurations of single walled (6,0) gold substituted SiC NTs, the energy gap decreases for the majority spin states decreases, and these systems exhibit a semimetallic behavior. From the density of states analysis, we observed that the electron orbitals arise from contributions from the C p orbitals and the 4d transition metal d orbitals. First principles results of total energy predicted the stability of the antiferromagnetic phase.